Menavigasi Tuntutan Akademik dan Spiritual melalui Wasatiyah: Integrasi Psikologi, Pendidikan Islam, dan Kesehatan Mental dalam Pendekatan MTI - Eko Ngabdul Shodikin; Muhammad Aji Nugroho; Zakiyuddin Baidhawy (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
Coping studies of Muslim students have been dominated by Western secular psychological theories that often fail to capture the complexity of Islamic spirituality, leaving a conceptual gap in academic stress resolution. Filling this gap, this study explores the integration of wasatiyah, which is based on the Qur'anic conception of the balance of the community (ummatan wasatan), as a coping instrument in managing the duality of academic demands and ritual obligations in Islamic Religious Higher Education (PTKI). Using an Interpretative Phenomenological Analysis (IPA) approach, data were extracted through in-depth interviews with seven STITMA Yogyakarta students. The analysis identified three essential themes: (1) internal ambivalence due to academic-spiritual role conflict; (2) reconstruction of meaning that transforms the perception of academic burden into worship (hifdz al-'aql) based on Maqasid Syariah; and (3) implementation of adaptive coping such as proportional time-blocking and integration of intentions. These findings confirm the novelty that wasatiyah is not merely a sociopolitical discourse, but an indigenous coping model that is effective in resolving students' identity crises. This study recommends that PTKI institutions integrate the wasatiyah coping model into integrated student development services and Islamic counseling guidance modules, in order to produce graduates who are academically strong and mentally stable.